The Movement in Resistance against Eye Aggressions by MOCAO as a social movement for justice, reparation and the right to peace and freedom in Colombia - Guerrero Rubiano, Andrés Juan; Bernal Martínez , Daniel Antonio; Fonseca, Juan Pablo (Torture Journal, 2024)
The collective action of MOCAO, Movimiento en resistencia contra las agresiones oculares del ESMAD (Escuadrón Móvil Antidisturbios) is presented as a social strategy to demand access to justice and the fulfilment of guarantees of reparation and non-repetition in Colombia. A brief account is given of significant events in our trajectory as a social movement, together with our letter of petitions to the national government as victims and survivors of ocular aggressions in the framework of police violence. Although ESMAD today has been reformed under the name of the Unit for Dialogue and Maintenance of Order (UNDMO), we consider that there have not yet been structural changes to ensure that its function is related to protecting the constitutional right to social protest.